Komunitas fitoplankton di daerah estuaria Krueng Aceh, Kota Banda Aceh - Raudhatul Jannah; Zainal A. Muchlisin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. The study on the phytoplankton community in estuary area of Aceh River was done from August to October 2006. The objective of the present study was to evaluate the structure of the phytoplankton scatter hitam community in Aceh River post tsunami. Explorative survey was done at three sampling sites along the river. Sampling sites were determinated based on salinity zoning; 30 ppt, 18-30 ppt and 5-18 ppt. The results show that higher diversity of the phytoplankton was found at sampling site 1, while the lower diversity was recorded at sampling site 3. There were no dominancy of species at all of sampling locatios. Diversity index was ranged between 0.95 to 0.98 and its mean that the diversity is higher at all of stations, while similarity between station 1 and 2 was higher compared to others stations.There was no difference in division composition of phytoplankton post tsunami, however, the total species was increased post tsunami.Keywords: Abundance, diversity index, similarity index, and tsunami